Manajemen Konflik dan Cara Penanganan Konflik Dalam Organisasi Sekolah - Achmad Hasan Nasrudin; Firda Fitrotul Unsa; Firda Nur Aini; Imron Arifin; Maulana Amirul Adha (LP2M IAIN Sultan Amai Gorontalo, 2021)
This study aims to describe conflicts in an organization, what factors cause conflict, approaches to conflict handling, and the impact of conflict on organizational performance. This type of research is a literature study. The results of this study are (1) conflict can be interpreted with 3 meanings, namely positive, neutral, and negative meanings, (2) the factors that cause conflict can come from external and internal factors of individual organizations. Internal factors can be in the form of personality differences, stress, decreased productivity and so on. While external factors can be in the form of communication problems, limited resources, sexual harassment, and so on, (3) the approach to handling conflict requires leadership skills. There are eight conflicts handling approaches, namely, deliberation, interference by third parties, confrontation, bargaining (bargaining), compromise, mediation, conciliation and consultation, and increasing resources, and (4) the performance of an individual can be hampered due to conflict, however not all conflicts have a negative impact, conflict can have a positive impact if it can be managed appropriately.